The assessment of reliability generalisation of clinician-administered PTSD scale for DSM-5 (CAPS-5): a meta-analysis - Wojujutari, Ajele Kenni; Idemudia, Erhabor Sunday; Ugwu, Lawrence Ejike (Frontiers in Psychology, 2024)
Background The CAPS-5 is a reliable instrument for assessing PTSD symptoms, demonstrating strong consistency, validity, and reliability after a traumatic event. However, further research is warranted to explore the divergent validity of the CAPS-5 and its adaptation to diverse cultural contexts. Objective In this meta-analysis, we endeavoured to comprehensively evaluate the reliability generalization of the CAPS-5 across diverse populations and clinical contexts. Methods A reliability generalization meta-analysis on the psychometric properties of CAPS-5 was conducted, encompassing 15 studies. The original versions’ psychometric properties were systematically retrieved from databases including PubMed, PsychNet, Medline, CHAHL, ScienceDirect, Scopus, Web of Science, and Google Scholar, with a focus on studies published between 2013 and 2023. Two independent investigators evaluated study quality using QUADAS-2 and COSMIN RB, pre-registering the protocol in the Prospero database for transparency and minimizing bias risk. Results Meta-analysis reveals CAPS-5 global reliability (α = 0.92, 95% CI [0.90, 0.94]), z = 99.44, p < 0.05 across 15 studies, supporting consistent internal consistency. Subscale analysis shows variability in Reexperiencing (α = 0.82), Avoidance (α = 0.68), Cognition and Mood (α = 0.82), and Hyperarousal (α = 0.74), with an overall estimate of 0.77 (95% CI [0.70;0.83]). Language-dependent analysis highlights reliability variations (α range: 0.83 to 0.92) across Brazilian-Portuguese, Dutch, English, French, German, Korean, and Portuguese. Test–retest reliability demonstrates stability (r = 0.82, 95% CI [0.79; 0.85]), with overall convergent validity (r = 0.59, 95% CI [0.50;0.68]). Conclusion The meta-analysis affirms CAPS-5’s robust global and subscale reliability across studies and languages, with stable test–retest results. Moderator analysis finds no significant impact, yet substantial residual heterogeneity remains unexplained. Our findings contribute intricate insights into the psychometric properties of this instrument, offering a more complete understanding of its utility in PTSD assessment. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023483748.